GROUP OF WORDS-TO-GROUP OF WORDS COMMUNICATION SYSTEM: A COMMON SURVEY - Sushant kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Group of words is the primary element in communication. Communication creates a bridge between languages as well as community to express one’s thinking in front of other. In modern society, it can be used to communicate to machines and also to find solutions of our problem like query system. There are several researches based on group of words-to-group of words communication. It may be related to emotion, translation, group of words mention, group of words synthesis, agriculture related query system, mobile communication etc. In this paper, group of words mention, group of words synthesis and hybrid category and focus on methods, validation in recent research is discussed. It gives idea for development of the algorithm with high accuracy as well as low word error rate.